Spatial Distance and Mental Construal of Social Events - Fujita, Kentaro; Henderson, Marlone D.; Eng, Juliana; Trope, Yaacov; Liberman, Nira (Psychological Science, 2006)
Construal-level theory proposes that increasing the reported spatial distance of events leads individuals to represent the events by their central, abstract, global features (high-level construal) rather than by their peripheral, concrete, local features (low-level construal). Results of two experiments indicated that participants preferred to identify actions as ends rather than as means to a greater extent when these actions occurred at a spatially distant, as opposed to near, location (Study 1), and that they used more abstract language to recall spatially distant events, compared with near events (Study 2). These findings suggest that spatially distant events are associated with high-level construals, and that spatial distance can be conceptualized as a dimension of psychological distance.